Effect of Neuromuscular Electrical Stimulation on Brain-derived Neurotrophic Factor - Miyamoto, Toshiaki; Kou, Keihou; Yanamoto, Hideya; Hashimoto, Saya; Ikawa, Mai; Sekiyama, Takashi; Nakano, Yoshiki; Kashiwamura, Shin-ichiro; Takeda, Chisako; Fujioka, Hiroyuki (International Journal of Sports Medicine, 2018)
Brain-derived neurotrophic factor (BDNF) has been considered an essential mediator responsible for the beneficial effects of physical activity in preventing cognitive impairment. This study aimed at examining the effects of a single bout of neuromuscular electrical stimulation (NMES) on levels of BDNF in the plasma and on cognitive performance in healthy adult men. Thirteen healthy adult men participated in three experimental sessions. The first session was 30 min of NMES to both legs, the second was 30 min of cycling exercise at the intensity of 60% peak oxygen uptake, and the third was 30 min of complete rest. Blood was examined for plasma BDNF levels and glucose concentrations, and cognitive performance tests were performed before and after each session. A single bout of NMES significantly increased plasma BDNF levels (p<0.05), which were equivalent to the amount of plasma BDNF released during the exercise session (p>0.05). However, there were no significant changes in cognitive performance between the sessions (p>0.05). The present study found that a single bout of NMES significantly increased plasma BDNF to levels normally present during moderate voluntary exercise. Therefore, NMES could serve as an alternative method of exercise, and might shed light on individuals for whom voluntary physical exercise is contraindicated.
Keywords: Electrical muscle stimulation; physical activity; cognitive function; dementia